2016
DOI: 10.6113/jpe.2016.16.5.1678
|View full text |Cite
|
Sign up to set email alerts
|

Design of Capacitive Power Transfer Using a Class-E Resonant Inverter

Abstract: This paper presents a capacitive power transfer (CPT) system using a Class-E resonant inverter. A Class-E resonant inverter is chosen because of its ability to perform DC-to-AC inversion efficiently while significantly reducing switching losses. The proposed CPT system consists of an efficient Class-E resonant inverter and capacitive coupling formed by two flat rectangular transmitter and receiver plates. To understand CPT behavior, we study the effects of various coupling distances on output power performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…This can be clearly shown in [15] whereby in order to achieve efficiency of 98.44%, the gap between the capacitive coupling is as near as less than 1mm for basic circuit configuration with class E inverter. Besides, there was also an analysis regarding gap distance which concluded that as distance increases, the efficiency of the system represented by output voltage is tremendously decreases exponentially shown in Figure 2.…”
Section: Figure 1 Basic Cpt Systemmentioning
confidence: 93%
See 3 more Smart Citations
“…This can be clearly shown in [15] whereby in order to achieve efficiency of 98.44%, the gap between the capacitive coupling is as near as less than 1mm for basic circuit configuration with class E inverter. Besides, there was also an analysis regarding gap distance which concluded that as distance increases, the efficiency of the system represented by output voltage is tremendously decreases exponentially shown in Figure 2.…”
Section: Figure 1 Basic Cpt Systemmentioning
confidence: 93%
“…Moreover, as Table 1 and Table 6 to be compared, there are different values for the same components of series inductor L, the shunt capacitor Cs, and the series capacitor C 1 and C 2 . This is due to different equations that have been used to calculate the components' values, as displayed in Equations (8) to (15).…”
Section: Cpt System With Impedance Matching Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been widely used in traffic, consumer electronics, underwater, mining equipment, and so on. Compared to the traditional plug-in power supply system, the wireless power transfer (WPT) system can achieve mechanical and electrical isolation, minimize cable and socket applications, and ensure safe operation in harsh environments [1,2]. Especially in electric bus and energy storage tram charging, the WPT primary side coil winding can be buried under the existing platform, and achieve station charging.…”
Section: Introductionmentioning
confidence: 99%